2022
DOI: 10.3390/ma15134654
|View full text |Cite
|
Sign up to set email alerts
|

Dealumination and Characterization of Natural Mordenite-Rich Tuffs

Abstract: The present study evaluates the feasibility of partially dealuminated natural mordenite as a catalyst support by studying improvement in its textural properties. This is the first study that reports the dealumination of natural zeolite-based tuffs from Ecuador. For this purpose, mordenite-rich tuffs were obtained from deposits close to Guayaquil, Ecuador. The raw material was micronized in order to increase its surface, and treated with NH4Cl. NH4+ cation-exchanged samples were finally reacted with HCl(aq) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Low metal impurities were present on the zeolite, which was due to the activation by acid prior to modification. 54 Furthermore, 15.88% of carbon was detected in zeolite, and this condition was also reported by Gea et al 51 which reported that Sarulla natural zeolite had a considerable amount of carbon (20.27–23.25%). According to Table 1 , there was an increase in the nickel content up to 10.59%, which indicated that nickel had been successfully impregnated on the zeolite.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Low metal impurities were present on the zeolite, which was due to the activation by acid prior to modification. 54 Furthermore, 15.88% of carbon was detected in zeolite, and this condition was also reported by Gea et al 51 which reported that Sarulla natural zeolite had a considerable amount of carbon (20.27–23.25%). According to Table 1 , there was an increase in the nickel content up to 10.59%, which indicated that nickel had been successfully impregnated on the zeolite.…”
Section: Resultssupporting
confidence: 73%
“…Because the as-prepared zeolite was collected from nature, 3.01% of impurities such as alkali and transition metals were reasonably detected. Low metal impurities were present on the zeolite, which was due to the activation by acid prior to modification . Furthermore, 15.88% of carbon was detected in zeolite, and this condition was also reported by Gea et al which reported that Sarulla natural zeolite had a considerable amount of carbon (20.27–23.25%).…”
Section: Resultsmentioning
confidence: 99%